Heteromysis (Heteromysis) microps (Crustacea, Mysidae), a commensal species for Upogebia pusilla (Crustacea, Upogebiidae) in Arcachon Bay (NE Atlantic Ocean). Issue 1 (December 2016) - Lavesque, Nicolas; Pascal, Ludovic; Gouillieux, Benoit; Sorbe, Jean-Claude; Bachelet, Guy; Maire, Olivier
Abstract Background The mysidHeteromysis (Heteromysis )microps is reported for the first time in the Bay of Biscay. During surveys carried out between March and September 2015 in Arcachon Bay, mysid specimens were fortuitously collected fromUpogebia pusilla burrows. Results Details on morphology, colour pattern and behaviour ofH. microps are provided. Conclusions Commensalism was frequently mentioned forHeteromysis species but never reported forH. microps . In this study, commensalism seems to be proved between the mysid and its hostU. pusilla .